A comparative study on interior acoustical comfort towards Perodua's compact car model through Monte Carlo simulation method - Khairul Azmir Azuddin author (Institute of Engineering Mathematics, Universiti Malaysia Perlis, 2017)
The objectives in this study are explained as follows ; to produce an acoustical comfort index for each three (3) Perodua's compact cars ; to measure the level of noise in the cabin by employing the data mining approach ; to compare the interior noises for each three (3) Perodua's compact cars between each state/condition.